Viabilitas dan Vigor Bibit Pakcoy (Brassica rapa Subsp. Chinensis) dan Terung (Solanum melongena L). dengan Kombinasi Komposisi Media Peat Moss dan Vermicast - Jambak, Kelvin Darmawan; Barus, Wan Arfiani; Noor, Noor Sarinah Mohd (Agrotrop : Journal on Agriculture Science, 2025)
Viability and Vigor of Pak Choy ( Brassica rapa Subsp. Chinensis) and Eggplant ( Solanum melongena L.) Seedlings with a Combination of Peat Moss and Vermicast Media Composition. This study aimed to analyze the effects of peat moss and vermicast growing media compositions on the viability and vigor of pak choi and eggplant seedlings. Conducted in the MARDI (Malaysian Agricultural Research and Development Institute) screen house in September 2024, the objective was to determine the viability and vigor of these seedlings under varying peat moss and vermicast mixtures. The study employed a non-factorial randomized block design with three replications. Treatments consisted of ten media compositions: T1 (100% Peat Moss = Control), T2 (90% Peat Moss: 10% Vermicast), T3 (80% Peat Moss: 20% Vermicast), T4 (70% Peat Moss: 30% Vermicast), T5 (60% Peat Moss: 40% Vermicast), T6 (50% Peat Moss: 50% Vermicast), T7 (40% Peat Moss: 60% Vermicast), T8 (30% Peat Moss: 70% Vermicast), T9 (20% Peat Moss: 80% Vermicast), and T10 (10% Peat Moss: 90% Vermicast). Observed parameters included viability (germination rate) and vigor (seedling height, root length, fresh weight, and dry weight). The results demonstrated that peat moss combined with vermicast significantly enhanced seedling viability and vigor (fresh weight) compared to using either medium alone. The optimal ratios were found to be T6 (50% Peat Moss: 50% Vermicast) and T7 (40% Peat Moss: 60% Vermicast). The nutrient-rich physical and chemical properties of vermicast contributed to improved seedling growth. This combination proves to be an effective growing medium for pak choi and eggplant seedlings.